The Impact of COVID-19 on Supply Chain and Human Resource Management Practices and Future Marketing - Yas, Harith; Bandar Alsaud, Alanoud; Alsharm, Afnan; Alkaabi, Ahmed; AlAdeedi, Ayesha (International Journal of Supply Chain Management, 2020)
Abstract The increased prevalence of COVID-19 has had severe implications on the well-being of most organization and professionals most especially in the field of human resource management and marketing. This study focused on establishing the impact of COVID-19 on the different human resource practices and future marketing. It was established that the dynamics of work have greatly changed from the traditional way of working from the organization’s premises to working remotely at home. Consequently marketing has also shifted to different online platforms since physical contact with customers is currently prohibited in order to maintain in social distancing one way of preventing coronavirus. These changes have been associated with different negative implications and some positives as some professionals find it more flexible and convenient to work remotely. To cope with the current changing times, it is necessary for organization to adjust and adopt the new emerging technologies of working remotely and consequently implement strategic policies and procedures towards maintaining a steady flow.